Jamming in Embryogenesis and Cancer Progression - Blauth, Eliane; Kubitschke, Hans; Gottheil, Pablo; Grosser, Steffen; Käs, Josef A. (Frontiers in Physics, 2021)
The ability of tissues and cells to move and rearrange is central to a broad range of diverse biological processes, comprising tissue remodeling and rearrangement in embryogenesis, cell migration in wound healing or cancer progression. These processes are linked to a solid-to-liquid transition, also known as unjamming transition, which enables tissues to switch between a stable state and an active, motile state. Various mechanisms, i.e. proliferation and motility, are key drivers for the (un)jamming transition on the cellular scale. However, beyond the scope of these fundamental mechanisms of cells, the biomolecular mechanism of (un)jamming is still unclear. In embryogenesis the proliferation rate of cells is high and the number density is continuously increasing, which indicates a number-density-driven jamming; whereas on the other hand during tumor progression cells have to unjam in tissues that are already densely packed, which suggests a shape-driven unjamming transition. Here we review recent studies on jamming transitions during embyrogenesis and cancer progression and pursue the question of how they might be interlinked. We discuss the role of density and shape during the jamming transition, and different biological factors driving it.